1991
DOI: 10.1017/s0954102091000482
|View full text |Cite
|
Sign up to set email alerts
|

Limnological properties of Antarctic ponds during winter freezing

Abstract: Two shallow ponds at Cape Evans, Ross Island, were sampled at 1–2 week intervals, during winter freezing throughout the winter and during the subsequent melt period, to examine the physical and chemical conditions imposed on the biota during the year. Liquid water was first detected at the base of the ponds in late December. During the main summer melt period conductivities were less than 10 mS cm−1 with maximum daily temperatures around 5°C. The bottom waters became increasingly saline during freezing and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…Aqueous temperatures may occasionally rise above 5°C but are more typically around 0°C. During freeze-up, salts are excluded from the ice and the resultant brines may have temperatures that fall well below zero (13,14,29,48). Calculations based on production-to-biomass ratios have shown that the ice shelf mats are perennial, with the standing stock representing many years of microbial biomass accumulation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous temperatures may occasionally rise above 5°C but are more typically around 0°C. During freeze-up, salts are excluded from the ice and the resultant brines may have temperatures that fall well below zero (13,14,29,48). Calculations based on production-to-biomass ratios have shown that the ice shelf mats are perennial, with the standing stock representing many years of microbial biomass accumulation (29).…”
Section: Discussionmentioning
confidence: 99%
“…CDOM exclusion likely results from the same process that affects other solutes-that is the tendency for ice to grow pure ice crystals, rejecting impurities during the process (Adams 1981;Welch and Legault 1986;Schmidt et al 1991;Wharton et al 1993). The lowest a CDOM in the ice covers was observed in the clear ice, although the bottom section of ice often had an exclusion factor slightly lower than the remaining clear ice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these are enriched by skuas and/or penguins, as well as sea spray. A study of the winter limnology of two such ponds has shown that the benthos experiences especially harsh conditions during freeze-up (Schmidt et al, 1991). These ponds had conductivities of a few hundred ktS cm -1 during summer, but salts were oncentrated into the remaining water during ice formation, ultimately resulting .in a chloride-rich brine with conductivities more than five times that of seawater and liquid water temperaaues below -10°C.…”
Section: Pondsmentioning
confidence: 99%
“…Most of the ponds are lined with cohesive mats of cyanobacteria, and planktonic chlorophyll a concentrations range from less than 1 ~g 1-1, to more than 100~tg 1 -I (Howard-Williams et al, 1991). A detailed survey of the algal benthos revealed 58 taxa, with 17 of these occurring in more than 25% of the samples (Howard-Williams et ai., 1990).…”
Section: Pondsmentioning
confidence: 99%
See 1 more Smart Citation